2021
DOI: 10.3389/fgene.2021.676136
|View full text |Cite
|
Sign up to set email alerts
|

Causal Inference Between Chronic Periodontitis and Chronic Kidney Disease: A Bidirectional Mendelian Randomization Analysis in a European Population

Abstract: BackgroundPrevious epidemiological studies have shown significant associations between chronic periodontitis (CP) and chronic kidney disease (CKD), but the causal relationship remains uncertain. Aiming to examine the causal relationship between these two diseases, we conducted a bidirectional two-sample Mendelian randomization (MR) analysis with multiple MR methods.MethodsFor the casual effect of CP on CKD, we selected seven single-nucleotide polymorphisms (SNPs) specific to CP as genetic instrumental variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…A genetic analysis of CKD and periodontitis was done in 2019, and they did not nd a causal relationship [27]. Notably, our study reached the same conclusion using updated GWAS data in 2021.…”
Section: Discussionsupporting
confidence: 75%
“…A genetic analysis of CKD and periodontitis was done in 2019, and they did not nd a causal relationship [27]. Notably, our study reached the same conclusion using updated GWAS data in 2021.…”
Section: Discussionsupporting
confidence: 75%
“…Genetic predisposition does not seem to be an important pathogenic factor between PO and CKD: using genome-wide association studies, single nucleotide polymorphisms (SNP) identified as genetic causes of PO were not related to kidney function and vice versa, and multiple SNP identified as genetic causes of CKD were not associated with PO, using 2 large genetic databases of PO (Gene-Lifestyle Interactions in Dental Endpoints-GLIDE Consortium) and of CKD (Chronic Kidney Disease Genetics-CKDGen Consortium) [50].…”
Section: Potential Causality and Biderctional Determinismmentioning
confidence: 99%
“…Additionally, reduced oral health behavior and a decreased perception of oral health concerns, resulting in low utilization of dental health care, have been discussed to explain a relationship between periodontitis and kidney disease, especially in the end stage of kidney failure [6,7]. However, the recent literature discusses more and more a causal, potentially bidirectional relationship between both diseases [5,8,9]. As such, microbiological effects, originating from potentially periodontal pathogenic bacteria, which have the ability to translocate and have distal effects outside of the periodontal pocket, have been discussed [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…The periodontitis-related increase in pro-inflammatory cytokines can also lead to an elevated systemic inflammation, potentially supporting renal atherosclerosis, renal deterioration, and end-stage renal disease development [8]. Another approach to explain the causality between periodontal and kidney diseases was an examination of genetic variables, especially single-nucleotide polymorphisms, whereby no causal relationship between both diseases has yet been confirmed [9]. However, the relationship between periodontitis and outcome of patients with kidney diseases, especially the risk of arteriosclerosis [11] or even mortality [12], supports the high relevance of this interrelationship as an issue of further research.…”
Section: Introductionmentioning
confidence: 99%